MEKANISME PENYALURAN DANA BANTUAN LANGSUNG TUNAI DI DESA SONOK KECAMATAN NONGGUNONG KABUPATEN SUMENEP PERSPEKTIF HUKUM ISLAM - Maulidah Maulidah; Abd. Rahman; Ach. Afin (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2023)
The Direct Cash Assistance (BLT) to Poor Households aims to assist the economy of impoverished communities due to the increase in fuel prices in October 2005. For the village of Sonok, the Direct Cash Assistance Program is provided to categorized poor communities, who are registered through the data collection by the Central Statistics Agency (BPS) in collaboration with the local government. Based on the above, the core issue is the Islamic Legal Perspective on the Mechanism of Distributing Direct Cash Assistance (BLT) Funds in the Village of Sonok. The research method used in this thesis is a qualitative method with a case study approach. To investigate the research problem, the researcher also employs a descriptive method towards primary and secondary data. The primary data for this thesis is obtained through interviews and documentation. Secondary data consists of information from other sources such as scholarly works, literature, encyclopedias, dictionaries, archives, and research findings related to the problem to be discussed or studied. From the research conducted, it was found that the BLT assistance has been distributed to both registered and unregistered individuals. As a result, those who receive the BLT assistance do not receive the full amount of 300,000 because of the addition of impoverished residents as per the policy of the local village government. The Islamic legal perspective on the distribution of the BLT funds prohibits this practice, as the existing assistance is intended only for those who are registered. Therefore, the assistance should only be given to them, as it is their rightful entitlement as registered recipients. Anything that is rightfully theirs should be conveyed to them, as it is a trust.